Hubungan Antara Self-Regulated Learning dengan Kecemasan Akademik Pada Peserta Didik - Herawati, Ira; Makhmudah, Ulya; Suryawati, Citra Tectona (Jurnal Psikoedukasi dan Konseling, 2023)
This study aims to identify the level of self-regulated learning, the level of academic anxiety, and to analyze the relationship between self-regulated learning and academic anxiety in class X students at vocational high school. This study uses a correlational quantitative approach. The subjects of this study amounted to 44 students. Data collection techniques used self-regulated learning scale instruments and academic anxiety scales. This study used descriptive statistical analysis and parametric inferential statistics with the support of the IBM SPSS version 25 Pearson Product Moment formula. The results of the descriptive analysis of this study show that the level of self-regulated learning and the level of academic anxiety are in the medium category. Meanwhile, the Pearson Product Moment analysis results obtained a significance value of 0.000 <0.05, then Ha is accepted which means there is a correlation between variable (X) and variable (Y) and the correlation coefficient value between self-regulated learning variables and academic anxiety is -0.742 which shows a negative relationship, meaning that the higher the self-regulated learning, the lower the academic anxiety of students, and vice versa, the lower the self-regulated learning, the higher the academic anxiety of students.